Impact of complete vaccination againts COVID-19 on lethality and deaths per million habitants in Oceania 06/05/2022 - Mora-Alvarado, Darner A. (2023)
This study addresses the impact of complete vaccination -with two doses- on case fatality rates and deaths/million inhabitants, due to COVID-19 up to 06/05/2022 in Oceania. To meet this objective, the nations of the continent are first located in the world; second, confirmed cases, deaths and lethality are described, according to continents; third, cases, deaths, lethality, deaths/million inhabitants, and complete vaccination were determined for each of the nations of Oceania. Fourth, the countries with the highest death rates in Oceania were classified and compared with the Ranking or “Top 10” of the nations with the highest mortality from COVID-19 in the world. Fifth, to evaluate the impact of vaccination, the correlation coefficient (r) was used at 95% confidence, between the percentages of vaccination, with lethality and deaths/million inhabitants. The results of the “r” value indicate that for lethality it was -0.45 and for the variable of deaths/million it was 0.32, which allows us to conclude that there is an inverse-qualified association with a “median” strength-between complete vaccination and lethality of the disease-deaths/confirmed cases*100-by COVID-19.